Characteristics of brain MRI abnormalities associated with symptomatic internal carotid artery stenosis: a retrospective single-center study - Usman, Frits S.; Kurniawan, Adrian; Pujiastono, Eko S.; Mianoki, Adika; Kastilong, Merlin P. (International Journal of Research in Medical Sciences, 2023)
Background: Carotid artery stenosis (CAS) may manifest with stroke, transient ischemic attack (TIA), or more covert non-hemispheric symptoms. While symptoms can be subtle, brain MRI abnormalities may already reflect substantial changes. This study aimed to determine the association between brain MRI abnormalities and symptomatic CAS. Methods: A retrospective cross-sectional study was conducted to subjects with symptomatic ICA stenosis admitted to a private secondary hospital in Jakarta, Indonesia, from January to December 2022. Symptoms were categorized to stroke/TIA and non-hemispheric symptoms (vertigo, headache, presyncope, etc.). Properties of CAS were recorded using digital subtraction angiography report. Brain abnormalities were recorded using MRI report. Results: Brain MRI abnormalities were detected in 96.2% CAS cases and similar between stroke (96.2%) and non-hemispheric symptoms (96.0%). The abnormalities tended to be in bilateral hemisphere (61.0%), predominantly periventricle (41.9%), basal ganglia (26.1%), and internal capsule for mild CAS (16.8%). Ipsilateral brain lesions were significantly associated with severe CAS (20.9% versus 10.8% for non-ipsilateral brain lesion, p=0.042) and stroke (45.9% versus 24.0% in non-hemispheric symptoms, p=0.035). Non-ipsilateral brain lesions were significantly associated with mild CAS (49.6% versus 40.7% for ipsilateral brain lesion, p=0.042) and non-hemispheric symptoms (72.0% versus 50.3% in stroke, p=0.035). Conclusions: Brain MRI abnormalities were very prevalent in CAS. There were no specific markers of brain MRI abnormalities associated with CAS. Brain abnormalities had been found since mild CAS, which presented in bilateral hemisphere as non-hemispheric symptoms. This study underlines the importance for the assessment of CAS in subjects since non-hemispheric symptoms with brain ischemic-related pathologies.